Analisis Perkembangan Motorik Kasar Melalui Permainan Menangkap dan Melempar Bola pada Anak Usia 5-6 Tahun - Herdini, Hafizah; Darmayanti, Nefi (EduInovasi: Journal of Basic Educational Studies, 2024)
Gross motor skills are good movement abilities in children which are very necessary in carrying out any activity. If this is not developed, children will become independent and become less confident in their social environment, each child will be able to reach the stage of gross motor development as long as they get optimal and appropriate stimulation. Through the activities of playing throwing and catching balls in gross motor development so that children have started to be able to make movements that coordinate between hands and feet in a simple way and can coordinate the muscles of the body. This study aims to find out how children's gross motor skills develop through throwing and catching balls in children aged 4-5 years at RA Arafah field, Medan sub-district. This research method uses descriptive qualitative research. Which aims to find out how the development of gross motor skills of children through playing throwing and catching balls at RA Arafah field Medan. This research is a descriptive qualitative research involving 1 teacher and 18 students. Data collection techniques used observation, interviews and documentation. Data analysis techniques carried out were data reduction, data display and drawing conclusions. Based on the results of the study, it was concluded that children's gross motor development can develop by playing catch and throwing balls. To maximize the development of gross motor skills, agility and dexterity in children, this game can strengthen muscles and improve their motor skills in general. This catching and throwing game activity can be used as a learning model in class and extracurricular activities that aim to improve children's gross motor skills. eywords: Gross Motor, Games, Child.